The NAC transcription factor CaNAC064 is a regulator of cold stress tolerance in peppers. (February 2020) - Hou, Xiao-ming; Zhang, Hua-feng; Liu, Su-ya; Wang, Xin-ke; Zhang, Yu-meng; Meng, Yuan-cheng; Luo, Dan; Chen, Ru-gang
Highlights: The expression of CaNAC064 was strongly induced by 4  ° C, 40  ° C, salicylic acid (SA) and abscisic acid (ABA). Down-regulated CaNAC064 reduced the tolerance of cold stress and overexpression of CaNAC064 increased the tolerance of cold stress. The Yeast Two-Hybrid and BIFC showed that the CaNAC064 interacted with the low temperature-induced haplo-proteinase proteins in plant cell. Abstract: NAC (NAM, ATAF1/2 and CUC2) proteins are plant-specific transcription factors (TFs) that are important in plant abiotic stress responses. In this study we isolated a NAC gene from Capsicum annuum leaves, designated as CaNAC064 . We characterized the amino acid sequence of CaNAC064 and found that it contain conserved domains of the NAC family, including a highly conserved N-terminus domain and a highly variable C-terminus domain. Expression analysis showed that the 4 0 C, 40 0 C, salicylic acid (SA) and abscisic acid (ABA) treatments strongly induced the expression of CaNAC064 through silencing of CaNAC064 in pepper and overexpressing in Arabidopsis. CaNAC06 4-silenced pepper plants exhibited more serious wilting, higher MDA contents and chilling injury index, lower proline content, and more accumulation of ROS in the leaves after cold stress. The CaNAC06 4-overexpressing Arabidopsis plants exhibited lower MDA content, chilling injury index and relative electrolyte leakage content as compared to WT plants under cold stress. Transcriptional activation activity analysis indicated that CaNAC064 has transcriptional activation activity in the 691–1071 bp key region. We identified 45 proteins that putatively interact with CaNAC064 using the Yeast Two-Hybrid method. According to the Yeast Two-Hybrid and BIFC results, CaNAC064 interacted with low temperature-induced haplo-proteinase proteins in plant cell. These results suggested that CaNAC064 positively modulates plant cold-tolerance, laying the foundation for future investigations into the role of NACs as regulatory proteins of cold tolerance in plants.